recipient and receiver Interrelational levels in the theatrical show (Journal of the College of Basic Education, 2023)
1- The problem of the inter-levels:Classification difference in form and language based on the literary formulations of the textsThe play is established according to the traditional methods of directing in the formality of the presentation, whereThese differences are manifested in the methods of performance, movement, and construction of the visual scene.Despite the many different interpretations and interpretations that may be based in manySometimes based on a source or a text by itself, classical presentations have aand contain its theoretic essence in order for it to be the classic itself as a showPerspective through the performance of its actors and the making of its characters and the establishment of its constructive vocabularyAnd the relationships between those vocabulary, as well as the romantic, natural, realistic, and otherOf those so-called theatrical doctrines.And because from the point of view of the rebel theatrical creators, thisStructural textual conditionalities that must be reflected on the formal constructivismFor display, a chain that imprisons artistic creativity in corners filled with repressed light, and I desireLighting innovative creative spaces different from what is prevalent. An act must be devised.What, or what, or other innovative methods in making a theatrical show,